2013
DOI: 10.1097/qai.0b013e3182a2d13c
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Maternal HIV-1 Disease Is Associated With Adverse Birth Outcomes in Malawian Women

Abstract: Background Compared to HIV-negative women, HIV-infected women have increased risk of low birth weight (LBW) and preterm delivery (PTD). We assessed whether severity of maternal HIV-1 disease was associated with LBW or PTD. Methods Secondary analysis of The Malaria and HIV in Pregnancy prospective cohort, which enrolled HIV-positive, pregnant Malawian women from 2000–2004. Included participants (n=809) were normotensive, antiretroviral treatment naïve women who delivered a live, singleton infant. Binomial reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
2
27
2
Order By: Relevance
“…In our study, we found an association between maternal plasma levels of sCD14 during the second half of pregnancy and low neonatal birthweight. This association persisted ( P = .043) in a multivariate regression model adjusted for demographic and clinical characteristics known to be potential risk factors for low birthweight . To our knowledge, this is the first time that this association is observed in low‐income countries, where the role of systemic immune activation markers may be confounded by other factors, such as malnutrition and maternal comorbidities, including opportunistic infections and/or vector transmissible diseases.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In our study, we found an association between maternal plasma levels of sCD14 during the second half of pregnancy and low neonatal birthweight. This association persisted ( P = .043) in a multivariate regression model adjusted for demographic and clinical characteristics known to be potential risk factors for low birthweight . To our knowledge, this is the first time that this association is observed in low‐income countries, where the role of systemic immune activation markers may be confounded by other factors, such as malnutrition and maternal comorbidities, including opportunistic infections and/or vector transmissible diseases.…”
Section: Discussionmentioning
confidence: 64%
“…The association between maternal levels of sCD14 and birthweight was tested using a multivariable linear regression model, controlling for potential confounding factors. The selection of potential confounding variables, including both demographic and clinical characteristics, was based on previous data and the available information in this study. Differences were considered statistically significant when P < .05.…”
Section: Methodsmentioning
confidence: 99%
“…(30-33) Yet, our stratified analysis findings demonstrating that women with STIs had higher rates of low birth weight and premature infants remained, even after controlling for infant HIV status. Those findings were also not explained by high rates of untreated maternal syphilis (10%), as they persisted in a second analysis controlling for this variable.…”
Section: Discussionmentioning
confidence: 83%
“…Given the link between immunodeficiency and adverse outcomes in prior studies [26-28] CD4 cell count was included as a covariate in all analyses. The remainder of covariates in adjusted analyses were determined through stepwise selection with retention of variables with p<0.2.…”
Section: Methodsmentioning
confidence: 99%